1991
DOI: 10.1164/ajrccm/144.5.1016
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid Resistance in Chronic Asthma: Glucocorticoid Pharmacokinetics, Glucocorticoid Receptor Characteristics, and Inhibition of Peripheral Blood T Cell Proliferation by GlucocorticoidsIn Vitro

Abstract: A total of 37 chronic, severe, nonsmoking asthmatic patients with documented reversible airways obstruction were classified as glucocorticoid-sensitive or -resistant on the basis of changes in FEV1, FVC, and peak expiratory flow (PEF) after oral prednisolone. The resistant patients showed no significant improvements in airflow limitation. Phytohemagglutinin (PHA)-induced proliferation of peripheral blood T lymphocytes from the sensitive but not the resistant asthmatic patients was significantly (p less than 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
152
3
2

Year Published

1992
1992
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(164 citation statements)
references
References 15 publications
7
152
3
2
Order By: Relevance
“…Consistent with previous observations [4], the refractoriness of PBMC from the current patients to dexamethasone inhibition underlines their relative glucocorticoid-insensitivity. It is unlikely that the chronic use of systemic glucocorticoids in these patients is responsible for this observation because after 8 weeks of treatment with MTX, during which the dose of glucocorticoids remained unaltered, the unresponsiveness of PBMC to dexamethasone was completely abrogated.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with previous observations [4], the refractoriness of PBMC from the current patients to dexamethasone inhibition underlines their relative glucocorticoid-insensitivity. It is unlikely that the chronic use of systemic glucocorticoids in these patients is responsible for this observation because after 8 weeks of treatment with MTX, during which the dose of glucocorticoids remained unaltered, the unresponsiveness of PBMC to dexamethasone was completely abrogated.…”
Section: Discussionsupporting
confidence: 91%
“…A proportion of these patients is found to be relatively resistant to the anti-inflammatory effects of glucocorticoids as judged by the reduced suppressive effects of dexamethasone on the proliferative response of peripheral blood mononuclear cells (PBMC) to the mitogen phytohaemagglutinin (PHA) [4] and increased peripheral blood T-cell activation [5]. Recently the authors have extended these observations to the bronchial mucosa by demonstrating the existence of increased mucosal T-cell activation in severe glucocorticoid-dependent asthmatics as compared to mild asthma and healthy control subjects [6].…”
mentioning
confidence: 99%
“…In patients with steroid-resistant and steroid-dependent asthma, the inhibitory effect of corticosteroids on cytokine release is reduced in peripheral blood mononuclear cells (60,61). In one group of patients, nuclear localization of glucocorticoid receptors in response to a high concentration of corticosteroids was impaired, and this may be due to such abnormalities as the increased activation of p38 MAP kinase described earlier.…”
Section: Molecular Mechanisms Of Corticosteroid Resistancementioning
confidence: 78%
“…50 Studies carried out in our laboratory and others have demonstrated that patients with GCresistant asthma have decreased cellular immune responses to GC. 51,52 These abnormalities involving their T cells, monocytes, and eosinophils make GC treatment less effective in suppressing the activation of cells from GC-resistant asthmatics than from GC-sensitive asthmatics.…”
Section: Pharmacogenetics Of Glucocorticoids In Asthmamentioning
confidence: 99%